PERAN ATRIBUT PRODUK DAN SIKAP MEREK TERHADAP PENINGKATAN EKUITAS MEREK - Utami Puji Lestari; Ella Anastasya Sinambela (Jurnal Ilmiah Satyagraha, 2023)
High brand equity becomes the company's strength to stay in themarket competition. Increasing brand equity is one of the company's strategiesthat is carried out all the time. Increasing the supporting factors of brand equityis a way to strengthen brand equity. This study aims to determine the role ofproduct attributes and brand attitudes in increasing brand equity. The researchpopulation is the consumer of the Rinnai brand gas stove. Obtained 85respondents as research samples with purposive sampling technique. Researchdata obtained through the distribution of questionnaires will then be analyzedusing multiple linear regression analysis. The results show that product attributesplay a significant role in the development of brand equity. Furthermore, brandequity is significantly influenced by brand attitudes. Product attributes and brandattitudes have a significant role in the joint formation of brand equity.